PENDIDIKAN DENGAN PENGABDIAN KULIAH KERJA NYATA DI KELURAHAN BULUH KASAP - Hikmal Kurniawan; Suci Irawati; Siska Amalia; Siti Rohani; Muhammad Lisman; Ilham Hudi (Journal of Community Service (JCOS), 2024)
A golden Indonesia in 2045 has become the hope of the Indonesian people, this is not without reason because Indonesia is experiencing a demographic bonus for the productive age group. Of course, the young people of Indonesia can continue the leadership of the nation and are able to be creative, independent and innovative. However, this will actually backfire if young people are unable to work and their thinking is damaged by pornographic videos, online gambling, drugs and bullying which robs the future of the nation's young generation. So, to help reduce the occurrence of this problem, we implemented a drug education program involving MAS Al-Huda teachers, the Head of BNN, and the Head of Buluh Kasap Subdistrict in outreach activities about the dangers of drugs and the dangers of bullying at school. Through education about the dangers of drugs and bullying, as well as trying to equip young people with the necessary knowledge and skills so that they can avoid these risks and focus on developing their potential positively. It is hoped that with this outreach, the younger generation will be better prepared to face challenges and contribute optimally to the nation's development in the future.